Pendidikan Anak dalam Keluarga: Telaah Literatur terhadap Peran Ayah dan Ibu di Era Modern - Qalbi, Nurul; Syam, Rezki Ayu Amaliyah (JURNAL PENA, 2025)
The role of parents in children's education is the main foundation in the formation of children's character and intelligence. This study aims to examine in depth the role of fathers and mothers in educating children in the modern era through a qualitative approach with a library research method. Data were collected from various academic sources and analyzed using the Miles and Huberman approach, namely data condensation, data presentation, verification, and conclusion drawing. The results showed that the role of fathers is not limited to breadwinners, but as role models who educate through example, emotional involvement, supervision, and fulfillment of children's psychological needs. The absence of the father's role is proven to have a negative impact on children's social and academic development. On the other hand, mothers play an integral role in the aspects of nurture, love and care - including intellectual stimulation, provision of affection, and physical and moral nurturing. The modern era presents new challenges such as the lack of family interaction time due to work pressures and the influence of digital media that reduces parental involvement. Therefore, the synergy of the roles of fathers and mothers is key in shaping a conducive educational environment at home. This study emphasizes the importance of a balanced division of time and roles between fathers and mothers so that children's education remains optimal amid social and technological changes.   References Abdul, Moh. R. (2020). Ibu Sebagai Madrasah Bagi Anaknya: Pemikiran Pendidikan R.A. Kartini. Journal of Islamic Education Policy, 5(2), 91–99. Retrieved from https://harakah.id/ketika-kartini-belajar-islam-dan-al-quran-kepada-kiai-soleh-darat/ Adilla, U. (2020). Analisis Peran Orang Tua Dalam Pendidikan Anak Menurut Islam Dalam QS. Luqman. Juridikdas Jurnal Riset Pendidikan Dasar, 3(3). Adilla, U. (2020). Analisis Peran Orang Tua Dalam Pendidikan Anak Menurut Islam Dalam QS. Luqman. Juridikdas Jurnal Riset Pendidikan Dasar, 3(3). Al, R., & Priyanti, N. (2021). Pengaruh Peran Ayah Terhadap Adaptasi Sosial Pada Anak Usia Dini Di Yayasan Nurmala Hati Jakarta Timur. Jurnal Pendidikan Anak Usia Dini, 6(2), 165–178. Alifiani, & Widodo, G. S. (2022). Pendampingan Belajar Tingkat Lanjut Melalui Pemberdayaan Orang Tua Asuh Advanced Learning Assistance Through Empowering Foster Parents. Abdimas Galuh, 4(2), 1231–1239. Retrieved from https://keckedungkandang.malangkota.go.id/, Arellanes, J. A., Miller, K., & Wesselmann, E. D. (2025). A Mixed Methods Investigation into Latino Fathers’ Roles in Their Children’s Educational Expectations. Journal of Latinos and Education, 24(2), 468–481. https://doi.org/10.1080/15348431.2024.2388635 Aziza, N. (2020). Kesiapan Ibu Dalam Perannya Sebagai Pendidik Anak Untuk Mempersiapkan Masa Depan Bangsa. Martabat: Jurnal Perempuan Dan Anak, 4(2), 251–266. https://doi.org/10.21274/martabat.2020.4.2.251-266 Bahri, S., Thahira, Y., & Taqwadin, D. A. (2024). Father’s Role and Character Education: A Reflective Analysis of the Qur’anic Stories. Jurnal Ilmiah Islam Futura, 24(2), 102–128. https://doi.org/10.1007/s10560-018-0558-0 Faradillah, F., & Mashudi, E. A. (2025). Keterlibatan Peran Ayah Terhadap Perkembangan Kognitif Anak Usia Dini. Kumaracitta : Jurnal Pendidikan Anak Usia Dini, 2(2), 85–103. Retrieved from https://ejournal.windari.com/index.php/kum Fathoni, T. (2023). Mengintegrasikan Konsep Vygotsky dalam Pendidikan Islam: Upaya Orang Tua dalam Memaksimalkan Potensi Anak. Muaddib: Jurnal Pendidikan Agama Islam, 1(1). Fathoni, T. (2023). Mengintegrasikan Konsep Vygotsky dalam Pendidikan Islam: Upaya Orang Tua dalam Memaksimalkan Potensi Anak. Muaddib: Jurnal Pendidikan Agama Islam, 1(1). Feriyanti, Y. G., Sari, D., & Asni, N. (2025). Peran Ibu Dalam Rumah Tangga Dalam Meningkatkatkan Prestasi Anak. Jurnal Pendidikan Dan Keguruan, 2(1), 84–98. Retrieved from https://ejournal.yayasanbhz.org/index.php/AhsaniTaqwim Husnaniyah, D., Yulyanti, D., & Rudiansyah. (2020). Hubungan Tingkat Pendidikan Ibu dengan Kejadian Stunting. The Indonesian Journal of Health Science, 12(1), 57–64. Istiyati, S., Nuzuliana, R., & Shalihah, M. (2020). Gambaran Peran Ayah dalam Pengasuhan The Discription Of Father’s Role In Caring The Children. PROFESI (Profesional Islam): Media Publikasi Penelitian, 17(1), 12–20. Kurniawaty, I., Faiz, A., & Yustika, M. (2021). Pemberian Motivasi Belajar pada Anak Melalui Peran Orang Tua. Jurnal Basicedu, 6(1), 34–41. https://doi.org/10.31004/basicedu.v6i1.1869 Mauliani, P., & Lestari, G. D. (2025). Peran Ibu Untuk Meningkatkan Perkembangan Kognitif Anak Usia 2-Tahun di Desa Mojowarno Kabupaten Jombang. J+PLUS: Jurnal Mahasiswa Pendidikan Luar Sekolah, 14(1), 162–172. Miles, M. B., Huberman, A. M., & Saldana, J. (2014). Qualitative Data Analysis A Methods Sourcebook. New Delhi: SAGE Publications India Pvt. Ltd. Muslih, M. (2021). Peran Ibu Dalam Melatih Pengamalan Beragama Pada Anak Di Lingkungan Keluarga. Edunesia : Jurnal Ilmiah Pendidikan, 2(1), 162–170. https://doi.org/10.51276/edu.v2i1.103 Najwah, N. (2016). Kriteria Memilih Pasangan Hidup (Kajian hermeneutika hadis). Jurnal Studi Ilmu-Ilmu al-Qur’an Dan Hadis, 17(1), 97–121. Nopiyanti, H. R., & Husin, A. (2021). Keterlibatan Orang Tua dalam Pendidikan Anak pada Kelompok Bermain. Journal of Nonformal Education and Community Empowerment, 5(1), 1–8. https://doi.org/10.15294/pls.v5i1.46635 Nurmalasari, F., Fitrayani, N., Paramitha, W. D., & Azzahra, F. (2024). Dampak Ketiadaan Peran Ayah (Fatherless) terhadap Pencapaian Akademik Remaja: Kajian Sistematik. Jurnal Psikologi, 1(4), 14. https://doi.org/10.47134/pjp.v1i4.2567 Paccaud, A., Keller, R., Luder, R., Pastore, G., & Kunz, A. (2021). Satisfaction With the Collaboration Between Families and Schools – The Parent’s View. Frontiers in Education, 6, 1–13. https://doi.org/10.3389/feduc.2021.646878 Qalbi, N. (2025). The Islamic Perspective on Gender Education: Analyzing the Qur’an, Hadith, and Historical Context in Indonesia. Jurnal Hawa: Studi Pengarus Utamaan Gender Dan Anak, 7(1), 39–48. https://doi.org/10.29300/hawapsga.v7i1.8614 Rafi, M., Tarigan, arif, Mahabatul Ainiah, E., Lubis, A., Yunus Lubis, M., Mustika Amalia, D., … Anak, K. (2023). Peran Ayah Dalam Pembentukan Karakter Anak: Telaah Surah Luqman Ayat 12-14. GENERASI EMAS: Jurnal Pendidikan Islam Anak Usia Dini, 6(2), 78–94. Rizami, A., Nazirah, S., & Syahriah. (2024). Building The Foundation Of Family Education: Religious, Moral and Skills Aspects. Tajdid, 4(1), 2808–2117. Retrieved from https://journal.umbjm.ac.id/index.php/athfal Sairah, S., & Chandra, A. (2022). Daycare dan Keterlibatan Ayah pada Pengasuhan Anak. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(5), 4181–4188. https://doi.org/10.31004/obsesi.v6i5.2498 Sari, M., & Asmendri, A. (2020). Penelitian Kepustakaan (Library Research) dalam Penelitian Pendidikan IPA. Natural Science, 6(1), 41–53. https://doi.org/10.15548/nsc.v6i1.1555 Sitorus, M. A. (2024). Pendekatan Peran Orang Tua Di Satuan Pendidikan Anak Usia Dini. Demagogi: Journal of Social Sciences, Economics and Education, 2(1), 12–21. https://doi.org/10.61166/demagogi.v2i1.10 Supriani, Y., & Arifudin, O. (2023). Partisipasi Orang Tua Dalam Pendidikan Anak Usia Dini. Jurnal Plamboyan Edu (JPE), 1(1), 95–105. Supriani, Y., & Arifudin, O. (2023). Partisipasi Orang Tua Dalam Pendidikan Anak Usia Dini. Jurnal Plamboyan Edu (JPE), 1(1), 95–105. Susanti, N. Y., & Adawiyah, R. (2020). Hubungan Pengetahuan Ibu Tentang Stimulasi Perkembangan Anak Dengan Keterampilan Ibu Dalam Melakukan Stimulasi Perkembangan Anak. Journal for Quality in Women’s Health, 3(1), 67–71. https://doi.org/10.30994/jqwh.v3i1.52 Syabrianto, A., Ramadhani, A., Simanjuntak, D. O., Waedoyee, M. H., Amin, M., Yani, N. M., & Annisa, T. (2023). Pentingnya Peran Orang Tua Dalam Mendidik Anak Di Usia Remaja Untuk Mencegah Penyalahgunaan Narkoba. Jurnal Dinamika Sosial Budaya, 25(1), 351–354. Retrieved from https://journals.usm.ac.id/index.php/jdsb Wulandari, H., & Shafarani, M. U. D. (2023). Dampak Fatherless Terhadap Perkembangan Anak Usia Dini. Ceria:Jurnal Program Studi Pendidikan Anak Usia Dini, 12(1), 1–12. https://doi.org/http://dx.doi.org/10.31000/ceria.v12i1.9019 Yunita, I. (2019). Peran Ayah Dalam Pembinaan Karakter Anak Kajian Terhadap Pola Asuh Di Komunitas Home Education Aceh. Ar-Raniry, 6(1), 27–40. Zakariyah, A., & Hamid, A. (2020). Kolaborasi Peran Orang Tua dan Guru dalam Pembelajaran Pendidikan Agama Islam Berbasis Online di Rumah. Intizar, 26(1), 17–26. https://doi.org/10.19109/intizar.v26i1.5892